2014
DOI: 10.1002/2014jb011002
|View full text |Cite
|
Sign up to set email alerts
|

Varying seismic‐acoustic properties of the fluctuating lava lake at Villarrica volcano, Chile

Abstract: Villarrica volcano outgasses through an open lava lake, with bubbles ranging in size from submillimeter to several meters, the largest of which produce strombolian bursting events that are visible from the crater rim. Thousands of shallow strombolian events identified through seismic waveform cross correlation were found to produce discrete and repetitive long-period seismic and infrasonic signals. We identified variations of up to 0.7 s in seismic-acoustic arrival delay times between April and July 2010 at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 49 publications
4
65
1
Order By: Relevance
“…Johnson and Aster (2005) obtained high and stable VASR values at Erebus volcano and attributed this observation to the lava lake activity associated with repetitive source processes at the surface of a stable lava lake. The observed decrease of the AS amplitude ratio in the case of Nyiragongo is not in agreement with such a constant trend and is better explained by variable VASR as observed at Villarrica volcano by Richardson et al (2014) during fluctuating lava lake episodes.…”
Section: Resultscontrasting
confidence: 58%
See 3 more Smart Citations
“…Johnson and Aster (2005) obtained high and stable VASR values at Erebus volcano and attributed this observation to the lava lake activity associated with repetitive source processes at the surface of a stable lava lake. The observed decrease of the AS amplitude ratio in the case of Nyiragongo is not in agreement with such a constant trend and is better explained by variable VASR as observed at Villarrica volcano by Richardson et al (2014) during fluctuating lava lake episodes.…”
Section: Resultscontrasting
confidence: 58%
“…Two further attributes are of significance with respect to the lava lake level, namely the delay time of the infrasound arrival with respect to the seismic one and the frequency content of the infrasound events (Richardson et al, 2014;Johnson et al, 2018). Unfortunately, the delay time information, which is potentially useful for measuring the level of lava in a conduit (Ripepe et al, 2002;Johnson, 2007) is particularly affected by 6 km of propagation through the atmosphere (see section Identification of Repetitive Long-Period (LP) Seismo-Acoustic Events).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding observations to include other data types also facilitates the interpretation of LP source processes. Studies correlating seismic and infrasound data have revealed important linkages between shallow LP seismicity and the generation of infrasound at other open vent, basaltic systems, including Shishaldin [ Petersen and McNutt , ], Kīlauea [ Fee et al , ], and Villarrica [ Richardson et al , ]. Some forms of degassing also often accompany LP events, and correlating seismic and infrasound data with plume observations or gas chemistry allows further refinement of source models [e.g., Petersen and McNutt , ; Fee et al , ], although few studies include quantitative information about plume composition and emission rate.…”
Section: Introductionmentioning
confidence: 99%